Numerical reduction of self‐consistent field models of macromolecular systems. Issue 1 (October 2016) - Disterhoft, Alexej; Raasch, Thorsten; Schmid, Friederike
Abstract: We report on the first application of model reduction techniques to the numerical simulation of self‐consistent field (SCF) models for polymer melts at equilibrium. As a complement to the classical SCF iteration, the parametric reaction‐diffusion equations for the chain propagators are treated by a reduced basis (RB) approximation from spaces of bandlimited functions. Numerical examples in a spatially one‐dimensional, periodic setting show that the approach is feasible, although not all requirements of an orthodox RB scheme are satisfied. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)